2021
DOI: 10.1371/journal.pone.0256670
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes of microshunt implantation in pseudoexfoliation glaucoma

Abstract: Purpose To compare the safety and efficacy of microshunt implantation augmented with Mitomycin C in patients with pseudoexfoliation glaucoma (PEXG) and primary open-angle glaucoma (POAG). Methods In this retrospective, single centre, interventional study, 46 eyes of 41 patients with PEXG (20 eyes) and POAG (26 eyes) underwent microshunt implantation. Definition of failure was an intraocular pressure (IOP) lower than 5 or higher than 17mmHg on two consecutive visits, an IOP reduction lower than 20% on two con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 26 publications
1
23
3
1
Order By: Relevance
“…The panellists indicated that more evidence is also needed to determine if the device can be indicated for other forms of glaucoma and/or for patients with certain comorbidities, such as high hyperopia. However, there was consensus that the device might be suitable for patients with the off-label diagnosis of pseudoexfoliation, supporting recent research that has shown the PMS has similar efficacy for patients with POAG and those with pseudoexfoliation [21]. There was consensus that it is possible to perform the procedure in patients with high myopia, but there was some disagreement among the panellists regarding this approach.…”
Section: Patient Selection and Preoperative Considerationsmentioning
confidence: 91%
“…The panellists indicated that more evidence is also needed to determine if the device can be indicated for other forms of glaucoma and/or for patients with certain comorbidities, such as high hyperopia. However, there was consensus that the device might be suitable for patients with the off-label diagnosis of pseudoexfoliation, supporting recent research that has shown the PMS has similar efficacy for patients with POAG and those with pseudoexfoliation [21]. There was consensus that it is possible to perform the procedure in patients with high myopia, but there was some disagreement among the panellists regarding this approach.…”
Section: Patient Selection and Preoperative Considerationsmentioning
confidence: 91%
“…In addition to the management of POAG, this device may be used to treat XFG, angle-closure glaucoma, and normal-tension glaucoma. To date there is insufficient evidence for the role of MIGS in these forms of glaucoma, which are often refractory to medical therapy, and thus represent important, growing indications for all novel surgical options [ 8 , 35 ]. Results in XFG were similar to those in patients with POAG, although higher rates of transient hypotony and choroidal detachment were observed in the former [ 35 ].…”
Section: Emerging Role Of Microshunt In Clinical Practicementioning
confidence: 99%
“…To date there is insufficient evidence for the role of MIGS in these forms of glaucoma, which are often refractory to medical therapy, and thus represent important, growing indications for all novel surgical options [ 8 , 35 ]. Results in XFG were similar to those in patients with POAG, although higher rates of transient hypotony and choroidal detachment were observed in the former [ 35 ]. The MicroShunt, like other tubes, should be used with caution in cases with narrow angles, since proximity and contact with the corneal endothelium should be avoided.…”
Section: Emerging Role Of Microshunt In Clinical Practicementioning
confidence: 99%
“…Recent studies have suggested additional associations between certain patient characteristics and the development of choroidal effusions. Pseudoexfoliative glaucoma has been linked to a higher incidence of choroidal effusions, especially when compared with primary open angle glaucoma (POAG) [14 ▪▪ ,40,41]. Shin et al [40] also identified older age, pseudophakia and hypertension as risk factors for choroidal effusion development following Ahmed glaucoma valve implantation.…”
Section: Risk Factors For Choroidal Effusion Developmentmentioning
confidence: 99%